Design and implementation of the FST controller applied to a second-order identified system using the Nidaq USB-6008 - Rodríguez Bustinza, Ricardo (2006)
The present investigation work tries on the control of an analogical system of second order(process), the same one that has been implemented with circuit's operational amplifiers and electronic devices. The system has been built and designed taking like I model to the prototype of the function of transfer of a system of second order. To the process there is been incorporate a stage of white noise with the purpose of effect to experiencing the interference and technical implementing linear control, we used the FST (Finite Settling Time) control. The pattern of the process was obtained in experimental form, for it you apply the identification of parameters; the method using is the parameters of the adjustment of the curve for direct interpolation. The model of accuracy has been fundamental for the technique applied of controlling FST The action of controlling is guided to control the position due to arbitrary inputs. Those put imposed in this work they are: construction, identification, implementation and simulation in real time of the system. The experimental results demonstrate that the designed control sign can make that the output follow the imposed references efficiently.